Effect of solvents on phytochemical concentrations and antioxidant activity of Garcinia benthamiana stem bark extracts - See, Irene; Cheng, Gwendoline Lian Ee; Siau, Hui Mah; Jong, Vivien Yi Mian; Teh, Soek Sin (Taylor & Francis, 2017)
The effect of solvents of various polarities (hexane, chloroform, ethyl acetate, and methanol) on phytochemical concentrations and antioxidant activities of stem bark of Garcinia benthamiana were examined. A medium polar solvent, ethyl acetate, was the most efficient in extracting the phenolic components from G. benthamiana, followed by methanol. The ethyl acetate extract had high total phenolic concentrations and scavenging activity against 2,2-diphenyl-1-picylhydrazyl (DPPH) free radicals. Both the ethyl acetate and methanol extracts had strong reducing power and moderate ferrous ion chelating ability and inhibition of β-carotene bleaching.